70 yrs of marriage (Raton Range Raton, New Mexico, 1975)
Newspaper Article on the 70th Anniversary of Mr. and Mrs. Abel Martinez.
Master list item #: 80
File location is in the Raton File Cabinet
Keywords: Martinez, Abel; Martinez, (Mrs.); Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico